Impact of participant attrition on child injury outcome estimates: a longitudinal birth cohort study in Australia. Issue 6 (30th June 2017) - Cameron, Cate M; Osborne, Jodie M; Spinks, Anneliese B; Davey, Tamzyn M; Sipe, Neil; McClure, Roderick J
Abstract : Background: Longitudinal research is subject to participant attrition. Systemic differences between retained participants and those lost to attrition potentially bias prevalence of outcomes, as well as exposure-outcome associations. This study examines the impact of attrition on the prevalence of child injury outcomes and the association between sociodemographic factors and child injury. Methods: Participants were recruited as part of the Environments for Healthy Living (EFHL) birth cohort study. Baseline data were drawn from maternal surveys. Child injury outcome data were extracted from hospital records, 2006–2013. Participant attrition status was assessed up to 2014. Rates of injury-related episodes of care were calculated, taking into account exposure time and Poisson regression was performed to estimate exposure-outcome associations. Results: Of the 2222 participating families, 799 families (36.0%) had complete follow-up data. Those with incomplete data included 137 (6.2%) who withdrew, 308 (13.8%) were lost to follow-up and 978 families (44.0%) who were partial/non-responders. Families of lower socioeconomic status were less likely to have complete follow-up data (p<0.05). Systematic differences in attrition did not result in differential child injury outcomes or significant differences between the attrition and non-attrition groups in risk factor effect estimates. Participants who withdrew were the only group to demonstrate differences in child injury outcomes. Conclusion: This research suggests that even with considerable attrition, if the proportion of participants who withdraw is minimal, overall attrition is unlikely to affect the population prevalence estimate of child injury or measures of association between sociodemographic factors and child injury.